The Effectiveness of Problem Based Learning on Achievement and Students Higher Order Thinking Skills in Malay Language Essay Writing - Mahamod, Zamri; Mokter, Farah Adlina (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to look at the effectiveness of Problem Based Learning (PBL) towards achievement and Higher Order Thinking Skill (HOTS) students in Malay writing. This study focuses on critical thinking skills, problem solving skills, decision making skills and reasoning skills. This study uses the pre-test post- test control group design. The subjects were 54 students from two classes of form 3 in Sekolah Menengah Kebangsaan Agama, Melaka. 28 students participated as the treatment group where teaching and learning process was held in a classroom. The other 26 students identified as the experiment group were taught using PBL. There were eight hypotheses presented. The inference statistic used t-test to assess the hypotheses and to answer the questions that arise in the study. The findings showed that two null hypotheses were accepted. However, the other six hypotheses were rejected. Acceptance of the null hypothesis indicates that there was no significant difference in the achievement of pre-test for both the control group and treatment at an early stage. Rejection null hypothesis suggests that there are differences in the achievement of pre and post test for both the experimental and control groups. The implications of this study showed that the teaching and learning uses PBM effective because it can improve student achievement in writing Malay Language simultaneously improve student HOTS.